Archipelagic studies charting new waters - Batongbakal, Jay L., editor (Quezon City : UP Systemwide Network on Archipelagic and Ocean Studies, 1998)
In cooperation with the UP Center for Integrative and Development Studies (UP-CIDS)
Keywords: Archipelagoes -- Philippines